Analisis Potensi Dan Daya Saing Ekonomi Lokal Serta Kependudukan Dalam Pengembangan Ekonomi Kabupaten Bulungan, Kalimantan Utara - Joni Trisetio Putro (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
One indicator to measure the contribution of natural resources and human resources to economic development is to look at the economic potential. Gross Regional Domestic Product (GRDP) is a description of the economic growth of a region so that GRDP can be used to analyze the potential and competitiveness of a region's economy. In addition, population development also needs to be analyzed to understand the needs of the population in development. The study aims to identify potential economic sectors, as economic drivers in Bulungan district by analyzing population, potential and competitiveness of the local economy. Dependence on the mining sector, can be overcome by developing other sectors that have the potential as a driving sector. This study uses a quantitative research approach with a focus on population, potential and competitiveness of the local economy. The data used are GRDP data and population data of Bulungan Regency, which are adapted from the publications of the Bulungan Regency BPS. This study uses Location Quotient analysis, and Shift Share analysis, combined with population analysis. The results show that there are 8 sectors that have the potential to drive the economy. The sectors with fast growth and competitiveness are the electricity and gas procurement sector, the information and communication sector, the health services sector and social activities, and other service sectors. The Bulungan Regency Government needs to pay more attention to the sector of economic potential to further improve the welfare of the community.